DOA Estimation Method Based on Space-Time Coding Antennas With Orthogonal Codes - Fang, Zuqi; Zhou, Qunyan; Dai, Jun Yan; Qi, Zhen Jie; Zhang, Jianan; Cheng, Qiang; Cui, Tie Jun (IEEE transactions on antennas and propagation, 2024)
Recently, direction-of-arrival (DOA) estimation has been widely employed in wireless communication networks, electromagnetic (EM) environment management, and radar tracking. However, traditional DOA estimation algorithms and systems are based on multiple digital receivers with expensive hardware. To overcome this challenge, we propose a novel DOA estimation method based on a space-time coding antenna. With the aid of space-time coding antenna and orthogonal codes, the received signal of each antenna element can be reproduced with high accuracy, helping to obtain more information on the incident waves. In this case, traditional super-resolved DOA estimation algorithms can be employed to estimate more complicated signals using the space-time coding antenna. Compared to the previous studies on similar accuracy, the proposed method has lower complexity and higher flexibility due to the reproduction of complete element information and the use of multiple signal classification (MUSIC) algorithm. The method can operate in the azimuth angle between −60° and 60°, with angle estimation errors of less than 1.5°, the estimation RMSE of 0.7°, and high reliability for different modulated signals.